2019
DOI: 10.18203/2320-1770.ijrcog20190870
|View full text |Cite
|
Sign up to set email alerts
|

A study of abnormal semen parameters in infertile couples in Assam, India

Abstract: In addition to numerical and structural defects of spermatozoa, functional male partner defects like erectile and ejaculatory dysfunctions have also increased tremendously in the recent years. ABSTRACT Background:The importance of male factor contribution to infertility is well recognised. Semen analysis is an indispensable diagnostic tool in the evaluation of the male partners of infertile couples. Aim and objective of the study was conducted to determine the abnormalities in semen among male partners in infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…We considered 1,460 patients for this study and the prevalence of male infertility found was 56.5%. This result is comparable to 52% and 54.33 ± 2.08% as shown in a study by Bhaduri et al and Sharmila et al 2,10 In a report by WHO, primary infertility ranges between 3.9% and 16.8% in India, 5 whereas according to a study conducted by Zarger et al, it is 50%. However, in the current study, we found primary infertility to be 84.4% which is comparable to 82.48% and 84.1% from a report by Shamila et al and Juneja et al, respectively.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We considered 1,460 patients for this study and the prevalence of male infertility found was 56.5%. This result is comparable to 52% and 54.33 ± 2.08% as shown in a study by Bhaduri et al and Sharmila et al 2,10 In a report by WHO, primary infertility ranges between 3.9% and 16.8% in India, 5 whereas according to a study conducted by Zarger et al, it is 50%. However, in the current study, we found primary infertility to be 84.4% which is comparable to 82.48% and 84.1% from a report by Shamila et al and Juneja et al, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…However, in the current study, we found primary infertility to be 84.4% which is comparable to 82.48% and 84.1% from a report by Shamila et al and Juneja et al, respectively. 5,10 Majority of our patients belonged to 31-35 years of age and 55.8% had abnormal spermiogram which is comparable to 52% and 56.38%. 11,12 Our study showed that teratozoospermia (17.20%) was the most common sperm abnormality.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The causes of male factor infertility may be classified as pre-testicular, testicular and post testicular factors. [1][2][3][4][5] These factors usually result from abnormalities in the semen quantity or quality, hence, seminal fluid analysis for deficiencies in semen quality and quantity may be used as a surrogate measure of male fecundity. 2,5,6 This analysis includes semen volume and pH, microscopy for sperm concentration, count, motility, morphology, vitality, debris and agglutination and leucocyte count.…”
mentioning
confidence: 99%